Reducing emissions from deforestation and forest degradation in developing countries: meeting the main challenges ahead - Imme Scholz; Lars Schmidt (Deutsches Institut für Entwicklungspolitik (DIE), 2008)
As consensus on methodological issues related to Reducing Emissions from Deforestation and Forest Degradation in Developing Countries (REDD) is growing, UNFCCC talks can now move forward on policy approaches. The most important topics here are how to finance REDD and how to design a REDD transfer system. In both cases, policy design is of enormous relevance not only for REDD but for the integrity of the post- 2012 climate agreement as a whole. A full integration of REDD into the future International Emission Trading Scheme (IETS) would require industrialised countries to commit to emission reductions substantially higher than 25–40 % by 2020, compared to 1990, in order to achieve significant reductions from the two chief emission sources (fossil fuels and tropical deforestation). As long as high overall reduction targets are unlikely and unclear, full integration bears the risk of leading into dangerous climate change. Market-linked approaches are more adequate. Most promising are the proposals by the Climate Action Network International and Norway to use proceeds from sales of emission allowances from global or regional carbon markets. REDD transfer systems should be designed so as to address the underlying causes of deforestation; otherwise mitigation effects will not be permanent. This requires a broad range of country-specific policy reforms which cannot be dealt with at the level of the convention. Instead, the United Nations Convention on Climate Change (UNFCCC) should provide a guiding framework for the design of national transfer systems and delegate operation to a subsidiary body, such as a forest fund. Developing countries should submit REDD strategies and should be compensated on the basis of a set of individual performance indicators.
Keywords: 330